The changing distribution of malaria in the Brazilian Amazon, 2003-2004 and 2008-2009 - Duarte, Elisabeth Carmen (2014)
Introduction More than half of the malaria cases reported in the Americas are from the Brazilian Amazon region. While malaria is considered endemic in this region, its geographical distribution is extremely heterogeneous. Therefore, it is important to investigate the distribution of malaria and to determine regions whereby action might be necessary. Methods Changes in malaria indicators in all municipalities of the Brazilian Amazon between 2003-2004 and 2008-2009 were studied. The malaria indicators included the absolute number of malaria cases and deaths, the bi-annual parasite incidence (BPI), BPI ratios and differences, a Lorenz curve and Gini coefficients. Results During the study period, mortality from malaria remained low (0.02% deaths/case), the percent of municipalities that became malaria-free increased from 15.6% to 31.7%, and the Gini coefficient increased from 82% to 87%. In 2003, 10% of the municipalities with the highest BPI accumulated 67% of all malaria cases, compared with 2009, when 10% of the municipalities (with the highest BPI) had 80% of the malaria cases. Conclusions This study described an overall decrease in malaria transmission in the Brazilian Amazon region. As expected, an increased heterogeneity of malaria indicators was found, which reinforces the notion that a single strategy may not bring about uniformly good outcomes. The geographic clustering of municipalities identified as problem areas might help to define better intervention methods.